Anniversary Issue Editorial. (13th January 2016) - FRANK, MATTHEW; LUDLOW, PIERS; REINISCH, JESSICA
Abstract : This issue opens the twenty-fifth volume of Contemporary European History . In the journal's inaugural editorial in 1992, Kathleen Burk and Dick Geary noted that they were standing 'on the brink of a new Europe' – and what exciting times those were. Just two and a half years after the collapse of the Berlin Wall, and barely months after the formal dissolution of the Soviet Union, CEH came into existence at a time of radical change in Europe and beyond. With the treaties signed at Maastricht in 1992 and in Amsterdam in 1997 European integration accelerated apace. The European Community became a Union. The twelve became fifteen. From March 1995 the Schengen Agreement let people of any nationality travel freely between the seven participating countries without any passport controls at the borders. By the end of the decade, the Single Market was a reality, the Euro was about to be introduced and negotiations for EU membership of ten central and eastern European countries were well underway. The themes of the decade were (re)integration, federation, ever greater union. As Burk and Geary wrote in their 1992 editorial, 'year by year, the concept of Europe as both a geographical and an historical entity becomes more credible'.